1968
DOI: 10.1126/science.161.3846.1158
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysones and Analogs: Effects on Development and Reproduction of Insects

Abstract: Ingestion of certain synthetic ecdysone analogs inhibited larval growth and development in several species of insects, whereas 20-hydroxyecdysone was inactive or considerably less active. Natural 20-hydroxyecdysone and ponasterone A, and a synthetic ecdysone analog inhibited ovarian maturation and egg production in the adult housefly. These effects appeared to be related to hormonal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1969
1969
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…Conversely, treatment with the ecdysone receptor antagonist, cucurbitacin B, resulted in a significantly higher number of total offspring relative to controls (MW, n = 15; P = 0.003, day 1; P < 0.001, day 2), and the number of offspring was higher in the EcR dsRNA samples on day 1, although not significantly higher; no differences were seen on day 2 (MW, n = 15; P = 0.118 day 1; P = 0.272 day 2). The feeding of ecdysone or ecdysone analogs inhibits ovarian maturation and egg production in houseflies and other insects (18,32), so this repressive effect on offspring production in the first two experiments is likely mediated by the excess ecdysone, with the opposite effect in the latter two experiments. This expected reproductive effect is an independent indication that the aphids are, in fact, sensing the ecdysone manipulations.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, treatment with the ecdysone receptor antagonist, cucurbitacin B, resulted in a significantly higher number of total offspring relative to controls (MW, n = 15; P = 0.003, day 1; P < 0.001, day 2), and the number of offspring was higher in the EcR dsRNA samples on day 1, although not significantly higher; no differences were seen on day 2 (MW, n = 15; P = 0.118 day 1; P = 0.272 day 2). The feeding of ecdysone or ecdysone analogs inhibits ovarian maturation and egg production in houseflies and other insects (18,32), so this repressive effect on offspring production in the first two experiments is likely mediated by the excess ecdysone, with the opposite effect in the latter two experiments. This expected reproductive effect is an independent indication that the aphids are, in fact, sensing the ecdysone manipulations.…”
Section: Resultsmentioning
confidence: 99%
“…In terrestrial environments, there are many reports of substances produced by plants that interfere with the reproductive capacity of grazing animals and which act as a form of population control. For example, ingestion of certain phytoecdysones inhibits larval growth and development in several species of insects, as well as interferes with the breeding of domestic sheep and some wild bird populations (Robbins et al, 1968). Such anti-herbivore agents may be common in both aquatic and terrestrial habitats even though most of the attention has traditionally focussed on feeding deterrents and poisoning compounds.…”
Section: Chemical Defences In Phytoplanktonmentioning
confidence: 99%
“…However, evidence pointing to the defensive role of these compounds in fern-insect interactions is largely lacking. Balick et al (1978) found no correlation between tannin levels and the amount of insect damage to 26 species of tropical ferns, and the role of the phytoecdysones in preventing insect herbivory has not been substantiated with laboratory feeding tests (Robbins et al 1968;Hendrix 1977;Jones and Firn 1978). Cyanogenic glycosides are known to be toxic to many herbivores, but their distribution in ferns appears to be limited (Balick et al 1978).…”
Section: Feeding Habits Of Insects Attacking Fernsmentioning
confidence: 99%